DOMINASI ADAT TERHADAP INDEPENDENSI LAKI-LAKI DAN PEREMPUAN DALAM NOVEL KAWIN SASUKU KARYA JUNILAWATA RESDIA: PIERRE BOURDIEU - Putri, Hesti; Nensilianti, Nensilianti; Tuflih, Muhammad Alfian (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
This research aims to reveal patriarchal domination of women’s independence in capital. The type of research used is descriptive qualitative. The source of data for this research is the novel Kawin Sasuku by Junilawata Resdia which was published in 2020 by the publisher Lovrinz with a thickness of 152 pages. The results of this research show the existence of patriarchal domination through the role of Mamak Samsudin who has the cultural and symbolic capital to manage the lives of her nephews. Social capital can be seen in Farhan’s character, who has the trust of the Riani family, while Wati uses her sewing skills as non-material economic capital to fight patriarchal domination.